Caregiver-Reported Indicators of Communication and Social Functioning for Young Children Who Are Deaf or Hard of Hearing. (4th April 2018) - Patrick, Donald L; Edwards, Todd C; Kushalnagar, Poorna; Topolski, Tari; Schick, Brenda; Skalicky, Ann; Sie, Kathleen
Abstract: We elicited caregiver-reported observations of children aged 5–10 who were deaf or hard of hearing (DHH) that resulted in two age-specific instruments: Caregiver Report of Behaviors and Events (CROBE-DHH 5–7 and 8–10). These new instruments record observations on communication and social behaviors/events. In Study 1, 36 caregivers provided qualitative data on important content on what they were able to observe for instrument development and in Study 2, 271 provided data for studying cross-sectional measurement properties. Two modules resulted in 11 items for children age 5–7 and 15 items for children 8–10 years. Items showing good 7-day reproducibility (ICC over .70) and fair 4-week reproducibility (ICC over .50) were retained. Children with milder hearing loss received higher (better) scores. Items did not distinguish between those with or without cochlear implants. Analyses suggest that the instruments are best used as individual indicator items. In both age groups, caregivers reported youths missed out on family conversations and spent little time on their own. These content-validated indicators apply to all children with DHH. Further work will evaluate the usefulness of these indicators in evaluating change in communication and social behaviors, and the implications of results for intervention.